Educação sexual na escola com a participação da família e o uso de novas tecnologias da educação: um levantamento bibliográfico - Reis, Verônica Lima dos [UNESP]; Maia, Ana Cláudia Bortolozzi [UNESP] (My University, 2012)
This study investigated, by descriptive documental research, the intervention models in Sexual Education in the school with the participation of the family and use of new technologies. The methodological stages were: collects in bases of data, selection and reading of the studies and elaboration of thematic groupings, by the content analysis. Four thematic group were elaborated: 1) intervention models with professionals; 2) intervention models with adolescents; 3) intervention models with the direct participation of the family and 4) Appreciation of the family’s participation in sexual education. The analised articles prioritize the adolescent population, when descrive the intervention. Few studies consider the family as important to sexual education and the techniques of the computer science are not very explored as pedagogic resources.

Este estudo investiga, por meio da pesquisa documental descritiva, os modelos de intervenção em Educação Sexual na escola com a participação da família e uso de novas tecnologias. As etapas metodológicas foram: coleta em bases de dados, seleção e leitura dos estudos e elaboração de agrupamentos temáticos, a partir da análise de conteúdo. Foram elaborados quatro núcleos temáticos: 1) Modelos de intervenção com profissionais; 2) Modelos de intervenção com adolescentes; 3) Modelos de intervenção com a participação direta da família e 4) Apreciação da participação da família na educação sexual. Os artigos analisados priorizam a população adolescente, quando descrevem a intervenção. Poucos consideram a importância da família para a educação sexual e as técnicas da informática são pouco exploradas como recursos pedagógicos.
Sexual Education in the school with family’s participation and the use of Education’s new technologies: a bibliographical rising
Keywords: Sexual education; Intervention; Technology of the Education; Educação sexual; Intervenção; Tecnologia da Educação